2021
DOI: 10.1044/2021_jslhr-20-00406
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Language Difficulties, Peer Victimization, and Bully Perpetration From 3 Through 8 Years of Age: Results From a Population-Based Study

Abstract: Background and Purpose Schoolchildren with language difficulties experience more peer victimization compared to their typically developing (TD) peers. Whether these children also bully their peers (bully perpetration) more than TD children is unclear. Furthermore, little is known about peer victimization and bully perpetration among preschool children with language difficulties and how it may be related to different paths of language difficulties. This study aimed to investigate associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Regarding group differences, a greater proportion of participants with self‐reports of oral language difficulties experienced bullying victimisation at any point in their lives than a comparable control group. Therefore, our results evidence that people with language difficulties are at a higher risk for bullying victimisation, congruently with past research (Conti‐Ramsden & Botting, 2004 ; Knox & Conti‐Ramsden, 2003 , 2007 ; McCormack et al ., 2011 ; Øksendal et al ., 2021 ; Redmond, 2011 ; Savage, 2005 ; Sureda‐García et al ., 2021 ; van den Bedem et al ., 2018 ). The relation between bullying and language difficulties could be due to different reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding group differences, a greater proportion of participants with self‐reports of oral language difficulties experienced bullying victimisation at any point in their lives than a comparable control group. Therefore, our results evidence that people with language difficulties are at a higher risk for bullying victimisation, congruently with past research (Conti‐Ramsden & Botting, 2004 ; Knox & Conti‐Ramsden, 2003 , 2007 ; McCormack et al ., 2011 ; Øksendal et al ., 2021 ; Redmond, 2011 ; Savage, 2005 ; Sureda‐García et al ., 2021 ; van den Bedem et al ., 2018 ). The relation between bullying and language difficulties could be due to different reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning studies examining the relation between speech or language difficulties and bullying victimisation in children and adolescents, a recent study that analysed data from the Norwegian Mother, Father, and Child Cohort Study (22 628 children) reveals that poor language skills at 3 and 5 years old were related to peer victimisation at 5 and 8 years old (Øksendal et al ., 2021 ). Another study comparing the level of peer victimisation among 60 children aged 7–8 years with developmental language disorder (DLD; previously called specific language impairment, SLI), attention‐deficit/hyperactivity disorder (ADHD), or typical development (TD) revealed that children with DLD suffered significantly higher physical bullying behaviours than TD children, and presented a significant risk of peer victimisation (Redmond, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, literature demonstrated that failing in-group inclusion predicts school absences, long-term drop-out, and other social-emotional problems [12][13][14][15]. In turn, these factors predict unemployment, social exclusion, poverty, mental illnesses, psychiatric disorders [16][17][18], and bullying [19]. This latter factor, bullying, can cause immediate consequences in a child's life [19] and adverse outcomes in adulthood [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these factors predict unemployment, social exclusion, poverty, mental illnesses, psychiatric disorders [16][17][18], and bullying [19]. This latter factor, bullying, can cause immediate consequences in a child's life [19] and adverse outcomes in adulthood [20,21].…”
Section: Introductionmentioning
confidence: 99%